Analisis Gaya Komunikasi Irwanteam Hairdesign dalam Perspektif Communication Accomodation Theory (Jurnal Ilmu Komunikasi dan Bisnis, 2025)
Internal communication style is effectively applied in every organization or company, including in beauty salons. This research aims to analyze the internal communication style applied by Irwanteam Hairdesign in improving hairstylist competence. The theory used in this research is communication accommodation theory, which is a theory that explains how individuals adjust their communication style in interaction. The research method used is qualitative with a case study approach. Data was collected through field observations and interviews with five informants including three representatives of the management and two hairstylists who have attended the training. The results show that Irwanteam Hairdesign applies an assertive communication style that is developed with an adaptive nature, oriented to the recipient of the message with a family approach that remains professional. This strategy reflects the convergence principle of communication accommodation theory, where communication styles are adjusted based on individual characteristics such as seniority and learning style. Two-way vertical communication, the use of various communication channels, and a participatory evaluation system are important factors in the effectiveness of information delivery and hairstylist skill development. This research emphasizes that structured and audience-oriented internal communication can contribute to improving employee competencies in the beauty salon sector. The importance of the research results is also useful for other similar organizations as well.